Impact of vitamin D supplementation on the ocular surface in patients with vitamin d deficiency - Oncul, Hasan; Fuat Alakus, Mehmet; Caglayan, Mehtap; Yilmaz Oncul, Fatma; Dag, Umut; Arac, Esref (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the effect of vitamin D (vit D) supplementation on the ocular surface parameters in patients with vit D deficiency.Material and Methods: In total, 63 patients with serum vit D deficiency were included. Patients were treated with an oral dose of 300.000 IU cholecalciferol. The ocular surface disease index (OSDI) questionnaire, fluorescein tears breakup time (FBUT), Oxford score, and Schirmer’s 1 test were performed for all patients. The data was obtained initially and at 4, 8, and 12 weeks after vit D supplementation.Results: Forty-nine of the patients were female and 14 were male. The mean age was 30.8±9.7 (18–58) years. All 63 patients came to the first follow-up, 57 patients came to the second follow-up, and 48 patients came to the third follow-up. The OSDI and Oxford scores yielded statistically significant decreases, while Schirmer’s 1 test and FBUT values showed a statistically significant increase after treatment with vit D. A positive correlation was observed between vit D values and FBUT and Schirmer’s 1 values; there was a negative correlation between OSDI values (r=0.286 and p0.001, r=0.219 and p=0.032, r = -0.357 and p0.001, respectively). The dry eye findings improved significantly after vit D supplementation in all cases. Conclusion: During clinical follow-up, it is important to evaluate serum vit D levels in patients with dry eye syndrome (DES). Increasing their vit D levels will help clinicians to treat DES quickly and effectively.